2011
DOI: 10.1055/s-0031-1291321
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Intensity Influences Hypotension Following Concurrent Exercise Sessions

Abstract: The study investigated whether resistance and aerobic concurrent exercise (CE) with different intensities influenced postexercise hypotension (PEH). 21 healthy men (20.7±0.7 yr) performed 4 sessions: control [CTL 60 min of rest], and CE1, CE2, and CE3 consisting respectively of 2 sets of 6 exercises at 80% 1RM followed by 30 min of cycle ergometer exercise at 50%, 65%, and 80% of peak oxygen consumption (VO2peak). All sessions lasted approximately 60 min and began with resistance prior to aerobic sessions. Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 12 publications
4
27
0
12
Order By: Relevance
“…The authors found PEH in SBP at 30 and 45 minutes post exercise in the AT session followed by ST. Similar results were also found in the study of Keese, Farinatti, Pescatello, Cunha, and Monteiro (2012) in which the effect of the intensity of the concurrent training on BP found a significant difference in all the post-exercise intervals (minutes 10 to 120 with 10 minute intervals) in the three sessions tested. Keese, Farinatti, Pescatello, and Monteiro (2011) observed an ABP decrease in all the protocols between minutes 10 and 120, however, the protocol was performed at 65% of the VO2peak and 80% of 1RM, which differed from the present study, that used the working heart rate.…”
Section: Discussionsupporting
confidence: 88%
“…The authors found PEH in SBP at 30 and 45 minutes post exercise in the AT session followed by ST. Similar results were also found in the study of Keese, Farinatti, Pescatello, Cunha, and Monteiro (2012) in which the effect of the intensity of the concurrent training on BP found a significant difference in all the post-exercise intervals (minutes 10 to 120 with 10 minute intervals) in the three sessions tested. Keese, Farinatti, Pescatello, and Monteiro (2011) observed an ABP decrease in all the protocols between minutes 10 and 120, however, the protocol was performed at 65% of the VO2peak and 80% of 1RM, which differed from the present study, that used the working heart rate.…”
Section: Discussionsupporting
confidence: 88%
“…Essas reduções da PA após o exercício físico têm sido demonstradas em indivíduos hipertensos e normotensos, e após EA ou EF 8,[12][13][14][15][16][17] . De fato, mais recentemente, alguns estudos têm verificado que a HPE também pode ser obtida após a combinação do exercício aeróbio e de força [18][19][20] . No entanto, pelo nosso conhecimento, não há estudos que avaliaram se há uma melhor ordem de realização desses exercícios para a redução da PA pós-exercicio.…”
Section: Palavras-chave: Exercício Aeróbio; Exercício De Força; Hipotunclassified
“…Para a PAD, esta duração foi de 50 minutos. Em outro estudo, KEESE et al 20 , realizaram três sessões de exercício concorrente com intensidades de EA diferentes (50%, 65% e 80% do VO 2pico ) e observaram HPE mais prolongada na sessão mais intensa. Todavia, na sessão a 65% do VO 2pico , que mais se assemelha a metodologia do presente estudo, os autores relataram HPE de PAS até duas horas e de PAD até 40 minutos após o exercício.…”
Section: Variação (Mmhg)unclassified
“…In another study K et al 15 found PEH in three di erent concurrent exercise sessions (RE before AE), with di erent AE intensities (50%, 65% and 80% of VO 2peak ), and found a signi cant decrease in systolic blood pressure in all three sessions. However, the authors stated that the more intense the session was performed, the longer was the PEH e ect.…”
Section: Discussionmentioning
confidence: 93%
“…However, there is more evidence of PEH after AE when compared to RE, since AE promotes a PEH of higher magnitude and duration 14 . Nonetheless, there is still little evidence on the e ect of the combination of AE and RE on blood pressure, being this combination named concurrent exercise (CE) Recently, some authors have referred that CE promotes PEH [14][15][16] . However, there is a gap in literature when it comes to providing information about which order of execution would result in a more accentuated decrease in blood pressure.…”
Section: Introductionmentioning
confidence: 99%